Multiphase reactor and polymerization system hydrodynamics - Cheremisinoff, Nicholas P.; Abid, M. (Mohammed) (Advances in engineering fluid mechanics series.)
This volume of the Advances in Engineering Fluid Mechanics Series covers topics in hydrodynamics related to polymerization of elastomers and plastics. Emphasis is given to advanced concepts in multiphase reactor systems often used in the manufacturing of products. This volume is comprised of 30 chapters that address key subject areas such as multiphase mixing concepts, multicomponet reactors and the hydrodynamics associated with their operations, and slurry flow behavior associated with non-Newtonian flows.